Giant recurrent retroperitoneal liposarcoma initially presenting as inguinal hernia: Review of literature. - Leão, P (2012)
INTRODUCTION: Liposarcomas comprise around 15% of soft tissue tumors. These tumors of mesodermal origin arise as single tumors, present one histologic type and diverse locations (including the retroperitoneum). Diagnosis of liposarcomas of retroperitoneum is difficult because of this unspecific presentation and in 50-100% of the cases there is recurrence from residual tissue. PRESENTATION OF CASE: An 86 year old male patient was admitted in 1996 due to a right and voluminous inguinal hernia. During the herniaplasty, a right paratesticular tumor was isolated and removed. The histologic exam revealed a well-differentiated liposarcoma. A CT scan was performed and a large abdominal mass was detected. The patient underwent a laparotomy and an incomplete resection of the tumor was achieved. After the surgery the patient remained asymptomatic during a long period. Nine years later, the patient underwent another laparotomy with partial removal of the giant recurrent retroperitoneal liposarcoma. CONCLUSION: The purpose of this publication is to report the recurrence of giant retroperitoneal liposarcoma, which is an unusual presentation in surgery today. Furthermore, we would like to emphasize the long-term survival of this patient despite partial resection and the possibility of performing a re-resection in this type of cases.